PERSEPSI GURU TENTANG SUPERVISI KEPALA SEKOLAH, MOTIVASI KERJA DAN KINERJA GURU: STUDI DI SMK NEGERI 26 JAKARTA - Adisetia Permata; Sri Zulaihati; Achmad Fauzi (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2016)
This study aims to determine the relationship between the perception of the Supervision Principal and Work Motivation on Teacher Performace in SMK Negeri 26 Jakarta. The sampling technique was conducted by random samplimg. The attainable population in this research were all teacher in status PNS is 67 teachers. The sample used by the tabel Isaac and Michael is 58 teachers. The simple linier regression and resulted Å¶ = 0,048X1 + 0,074X2 + 69,062. Relationship between the teacher perception of supervision principal with teacher performance, and work motivation with teacher performance are significantly positive. In simultan, relationhip between teacher perception of supervision principal, work motivation with teacher performance are significantly positively correlated. Normality test result were calculate with SPSS shows that all the variables above 0,05, inicated normally distributed. In partial test, significance t hitung teacher perception of supervision principal and work motivation size is 5,405 with significance 0,000 so, it indicated possitive significantly related between them.